The Stability of Time- versus Money-based Product Evaluations - LEE, Leonard (Institutional Knowledge at Singapore Management University, 2011)
Consumers constantly make product decisions involving temporal and monetary considerations. In this work, we examine how consideration of these two fundamental economic resources influences the stability of product evaluations. Results from a series of seven experiments demonstrate that, despite prior research that has shown that the valuation of time is more ambiguous and context-dependent than the valuation of money, time-based product preferences tend to be more consistent than money-based product preferences. Our findings support an affect-based account: compared to monetary considerations, temporal considerations elicit greater reliance on feelings versus analytical evaluation, which facilitates holistic judgments and promotes preference consistency. Consequently, reliance on feeling (vs. thinking) when evaluating products based on monetary considerations can generate greater preference stability. Our experimental results also rule out alternative accounts based on differential decisional difficulty and attribute importance, as well as suggest new questions for future research.